Artful Research Approaches in #amwritingwithbaby: Qualitative Analysis of Academic Mothers on Facebook (LEARNing Landscapes, 2016)
This study contemplates one facet of academic motherhood through the use of artful research approaches in qualitative research to examine the (im)balance of being a mother writing academic works while raising and caring for a young child, as presented in an online hashtag Facebook campaign, #amwritingwithbaby. Speci cally, this study uses an analysis of online posts and arts-based representations of ndings through a comparison of narrative, poem, and word clouds. Through using popular media for representing the ndings, this study helps address the accessibility of artful inquiry into the growing body of works seeking equity for women and mothers in academia.
Keywords: equity; women; academia; motherhood; qualitative; narrative; poem; artful research